The Effect of Basic Swimming Skills Training on Gross Motor Skills in Autistic Children (7-11 Years Old) - Farnaz Torabi; Azar Aghayari; Sohayl Dashtabadi (University of Tehran, 2015)
The aim of this study was to investigate the effect of basic swimming skills training on gross motor skills in male autistic children (7-11 years old). For this purpose, 20 autistic children (mean + SD age: 10.3±1.05 yr and BMI: 18.9±1.76 kg/m2) were randomly divided into two groups of experimental and control (each group 10 subjects). The training protocol of the experimental group was implemented for 6 weeks containing warm-up with stretching exercises, standard swimming instruction and training and ball movements inside and outside water. The control group was engaged in their routine activities. At the beginning and at the end of the study, the second edition of Test of Gross Motor Development (TGMD-2) (Ulrich, 2000) was applied for both groups. Findings showed that the manipulation skills (%40), locomotion skills (%31) and gross skills (%35) improved significantly after the selected training protocol (P<0.05). Accordingly, the differences between the two groups in changes of pretest and posttest of the three skills were significant (P<0.05). Finally, it seems that swimming training with an emphasis on manipulation and locomotion skills can have beneficial effects on motor abilities of children with autism.